1993
DOI: 10.1016/0304-3959(93)90203-2
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of chronic pain patients: factor analysis of the MMPI-2

Abstract: The Minnesota Multiphasic Personality Inventory (MMPI) has been used extensively in the assessment of chronic pain patients. More recent studies using cluster-analytic techniques, investigation of sub-scales, and factor analysis have refined its usefulness. The present study factor-analyzed MMPI-2 data from a sample of 114 chronic pain patients from two different treatment programs. MMPI-2 t scores for the validity and clinical scales, as well as the Harris and Lingoes sub-scales for scales 1, 2 and 3, were us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0

Year Published

2000
2000
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 12 publications
0
10
0
Order By: Relevance
“…Although not longitudinal in design, the authors believe each of their factors may each represent one stage in the development of chronic pain [26].…”
Section: Mmpi To Distinguish Between "Functional" and "Organic" Painmentioning
confidence: 99%
See 1 more Smart Citation
“…Although not longitudinal in design, the authors believe each of their factors may each represent one stage in the development of chronic pain [26].…”
Section: Mmpi To Distinguish Between "Functional" and "Organic" Painmentioning
confidence: 99%
“…One recent study used a recently revised version of the MMPI, the MMPI-2 [25], to assess personality traits in patients with chronic pain [26] and found four interpretable factors that reflected 1) general psychological distress, 2) social isolation and introversion, 3) psychomotor retardation, and 4) physical dysfunction. Although not longitudinal in design, the authors believe each of their factors may each represent one stage in the development of chronic pain [26].…”
Section: Mmpi To Distinguish Between "Functional" and "Organic" Painmentioning
confidence: 99%
“…Personality has received attention, specifically regarding attempts to identify predisposing traits, as well as the ramifications of personality disorders for the experience of pain-related conditions. [20][21][22][23][24][25] The relationship between emotional disorders and chronic pain has also been extensively investigated. The literature tends to highlight depression and anxiety in this regard.…”
Section: Psychological Factors and Chronic Painmentioning
confidence: 99%
“…Although Keller and Butcher found these classifications useful, they cautioned that these subtypes classified only half of their total sample and may be overly restrictive in characterizing chronic pain patients. Deardorff et al (1993) also found that the four-cluster solution "generally resulted in poor classification rates when applied to other [than low-back pain] pain populations" (p. 153). Despite these limitations, the profile cluster subtypes appear promising in describing meaningful groups or types of self-presentations by chronic pain patients and warrant further research.…”
mentioning
confidence: 93%